2023
DOI: 10.1002/admt.202300572
|View full text |Cite
|
Sign up to set email alerts
|

Au Modified Hollow Cube Sn‐MOF Derivatives for Highly Sensitive, Great Selective, and Stable Detection of n‐Butanol at Room Temperature

Abstract: At present, there are still few gas sensors for detecting n‐butanol at room temperature. It is worth noting that detecting target gas at room temperature is beneficial to reduce energy consumption and prolong the lifetime of sensors. In this work, different molar ratios Au nanoparticles modified SnO2 derived from Sn‐MOF hollow cubes (Au‐SnO2) are synthesized by the coprecipitation method. The Au‐SnO2 has higher specific surface area than pure SnO2, which is conducive to improving gas sensing. The 0.7% Au‐SnO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Further examples of MOFs-derived porous MOSs are the nano-cubic-structured SnO 2 [53,54] and Fe 2 O 3 [55], both obtained through calcination and used to detect butanol efficiently and selectively. These recent publications demonstrated that MOFs can be used as useful templates to synthesize MOSs with outstanding peculiar morphologies, structures, and porosity for sensing applications.…”
Section: Metal Organic Framework (Mofs)mentioning
confidence: 99%
“…Further examples of MOFs-derived porous MOSs are the nano-cubic-structured SnO 2 [53,54] and Fe 2 O 3 [55], both obtained through calcination and used to detect butanol efficiently and selectively. These recent publications demonstrated that MOFs can be used as useful templates to synthesize MOSs with outstanding peculiar morphologies, structures, and porosity for sensing applications.…”
Section: Metal Organic Framework (Mofs)mentioning
confidence: 99%